“At the still point of the turning world:” T.S. Eliot and Gilles Deleuze - Zekiye ANTAKYALIOGLU (E-REA)
T.S. Eliot was a prominent poet-critic of the modernist period whose theories have still as much penetrating influence on contemporary thinking as his poetry. Eliot cannot be confined to a single period such as modernism when his affinity with various opposing schools of thinking is considered. The same is true for Gilles Deleuze who, as a unique and idiosyncratic philosopher resists any categorization. We identify postmodern tendencies in the modernism of Eliot in the same way as we identify modernist sensibilities in the poststructuralism of Deleuze. A comparison between Eliot’s views of time, memory and perception and those of Deleuze may bring to light some resemblances. One major element behind these resemblances is their indebtedness to Henri Bergson in the formation of their thought. Eliot’s concepts such as “objective correlative,” “dissociation of sensibility,” and “impersonal voice” echo the Deleuzean concept of art as the producer of “affects and percepts.” Gilles Deleuze is known for his analyses of modernist literature and Eliot, somehow, was not among his focus points. This paper will be a revisiting of T.S. Eliot’s ideas on art and time with Deleuze in mind, to illustrate the common points of the two figures.